2016
DOI: 10.1111/jpi.12368
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alleviates postinfarction cardiac remodeling and dysfunction by inhibiting Mst1

Abstract: Melatonin reportedly protects against several cardiovascular diseases including ischemia/reperfusion (I/R), atherosclerosis, and hypertension. The present study investigated the effects and mechanisms of melatonin on cardiomyocyte autophagy, apoptosis, and mitochondrial injury in the context of myocardial infarction (MI). We demonstrated that melatonin significantly alleviated cardiac dysfunction after MI. Four weeks after MI, echocardiography and Masson staining indicated that melatonin notably mitigated adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 67 publications
(141 reference statements)
3
72
0
Order By: Relevance
“…Accumulating studies indicate that melatonin have protective effects against DCM . Our previous study demonstrated that melatonin alleviated left ventricular remodeling and cardiac dysfunction after myocardial infarction . The mechanisms were associated with enhanced cardiomyocyte autophagy and reduced cardiomyocyte apoptosis.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Accumulating studies indicate that melatonin have protective effects against DCM . Our previous study demonstrated that melatonin alleviated left ventricular remodeling and cardiac dysfunction after myocardial infarction . The mechanisms were associated with enhanced cardiomyocyte autophagy and reduced cardiomyocyte apoptosis.…”
Section: Introductionmentioning
confidence: 89%
“…Melatonin was initially dissolved in absolute ethanol and then diluted in sterile water to a final concentration of 0.5% ethanol. After constructing the DM model, mice were daily orally gavaged with melatonin (20 mg/kg/day) for 4 weeks …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After homogenizing and centrifuging at 12 000  g for 15 minutes at 4°C, the supernatant was mixed with the working reagent and then assessed by a microplate luminescence luminometer. As before, the contents of ROS were assessed by electron paramagnetic resonance spectroscopy according to Mellin's methods 41. Data were representative of three biological repeats.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, melatonin was closely related with reverse remodeling after cardiac resynchronization therapy in patients with heart failure and ventricular dyssynchrony [260]. Furthermore, it was observed that melatonin could markedly improve cardiac dysfunction, mitigate cardiac remodeling after myocardial infarction, increase the level of autophagy, attenuate apoptosis, regulate the integrity and restore the function of mitochondria through the inhibition of mammalian Ste20-like kinase 1 (Mst1) and the promotion of SIRT1, indicating the Mst1/SIRT1 signaling was involved [261]. …”
Section: Bioactivities Of Melatoninmentioning
confidence: 99%